1986
DOI: 10.1523/jneurosci.06-03-00644.1986
|View full text |Cite
|
Sign up to set email alerts
|

Dynorphin- and enkephalin-like immunoreactivity is altered in limbic- basal ganglia regions of rat brain after repeated electroconvulsive shock

Abstract: In an attempt to determine whether the opioid peptides derived from prodynorphin participate in the effects of electroconvulsive shock (ECS), we used radioimmunoassay and immunocytochemistry to measure dynorphin-like immunoreactivity (DN-LI) in various rat brain regions after repeated ECS treatments. Ten daily ECSs caused a significant increase in dynorphin A (1-8)-LI in most limbic-basal ganglia structures, including hypothalamus (50%), striatum (30%), and septum (30%). No significant change was found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…In contrast, the influence of seizures on dynorphin immunoreactivity has been less consistent; instances of increase (Iadarola et al, 1986;Kanamatsu et al, 1986b) and decrease (Iadarola et al, 1986;Kanamatsu et al, 1986a;McGinty et al, 1986) have both been reported.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, the influence of seizures on dynorphin immunoreactivity has been less consistent; instances of increase (Iadarola et al, 1986;Kanamatsu et al, 1986b) and decrease (Iadarola et al, 1986;Kanamatsu et al, 1986a;McGinty et al, 1986) have both been reported.…”
mentioning
confidence: 95%
“…The opioid peptides have been most extensively studied in this regard. Several treatments that induce recurrent or prolonged seizure activity, including repeated electroconvulsive shock (ECS) (Yoshikawa et al, 1985;Kanamatsu et al, 1986a), intracerebral kainic acid (Hong et al, 1980;Gall et al, 198 lb;McGinty et al, 1983;Kanamatsu et al, 1986b), and chemical and electrical kindling (Vindrola et al, 198 1, 1984;Iadarola et al, 1986;McGinty et al, 1986) have been found to elevate enkephalin levels in a number of brain areas, with some differences in the regional distribution of increased enkephalinlike immunoreactivity (ENK-I) between treatments. Work in this laboratory has demonstrated that recurrent seizure activity induced by small electrolytic lesions in the hilus of the dentate Figure 1.…”
mentioning
confidence: 99%
“…Changes in a variety of neuropeptides and peptide growth factors are associated with depression (Kubek et al 1985;Widerlöv et al 1986;Kanamatsu et al 1986;Stenfors et al 1989;Orzi et al 1990;Zetterstrom et al 1998;Mathe 1999;Pekary et al 1999Pekary et al , 2000. For example, depressed patients have decreased levels of cerebrospinal fluid neuropeptide Y (NPY) (Widerlöv et al 1986(Widerlöv et al , 1988Gjerris et al 1992).…”
mentioning
confidence: 99%
“…ECS was performed as reported previously. 5) Briefly, ECS was administered via ear-clip electrodes (35 mA, 0.5 s) to induce a typical clonic-tonic seizure lasting 5-10 s. In acute experiments, the animals were decapitated 1, 3,6,12,24,48, and 72 h after a single ECS. In chronic experiments, ECS was administered every other day, totaling six shocks.…”
Section: Electroconvulsive Shockmentioning
confidence: 99%